Free-breathing contrast-enhanced upper abdominal MRI in children: comparison between Cartesian acquisition and stack-of-stars acquisition with two different fat-suppression techniques. (April 2021) - Kim, Jeong Rye; Yoon, Hee Mang; Cho, Young Ah; Lee, Jin Seong; Jung, Ah Young
Background: Respiratory artifacts impair image quality of magnetic resonance imaging (MRI) in children who cannot hold breath during MRI examination. Purpose: To compare the quality of free-breathing contrast-enhanced 3D T1-weighted (T1W) images of the upper abdomen in children using Cartesian acquisition (Cartesian eTHRIVE), stack-of-stars acquisition with spectral fat suppression (3D VANE eTHRIVE), and stack-of-stars acquisition with fat suppression using modified Dixon (3D VANE mDixon). Material and Methods: Pediatric patients (aged <19 years) who underwent whole-body MRI with free-breathing contrast-enhanced T1W axial scans of upper abdomen using Cartesian eTHRIVE, 3D VANE eTHRIVE, and 3D VANE mDixon were enrolled. Image quality parameters were assessed including overall image quality, hepatic edge sharpness, hepatic vessel clarity, respiratory artifacts, radial artifacts, lesion conspicuity, and lesion edge sharpness using the Likert scale, where a lower score indicated poorer image quality. The coefficients of variation of signal intensity of liver and spleen were analyzed. Results: In 41 patients, 3D VANE eTHRIVE showed the highest scores for all image quality parameters ( P ≤ 0.001). 3D VANE eTHRIVE also showed higher scores for respiratory ( P ≤ 0.001) and radial artefacts than 3D VANE mDixon ( P = 0.001). There were no significant differences in coefficients of variation of signal intensity of the liver and spleen between 3D VANE eTHRIVE and 3D VANE mDixon. Acquisition time was longer for 3D VANE eTHRIVE (81.26 ± 16 s) than for Cartesian eTHRIVE (7.87 ± 0.95 s) and 3D VANE mDixon (76.66 ± 12.4 s, P < 0.001). Conclusion: The application of stack-of-stars acquisition to 3D T1W abdominal MRI resulted in better image quality than Cartesian acquisition in free-breathing children. In stack-of-stars acquisition, spectral fat suppression resulted in better image quality and fewer artifacts than mDixon.